Hubungan Sekolah, Orang Tua, dan Masyarakat di Sekolah Dasar untuk Meningkatkan Kualitas Sekolah - Anggraini, Febiyana; Nurhasanah, Nurhasanah (TSAQOFAH, 2024)
Schools are educational institutions that have a very important role in creating a generation that is superior, qualified and able to compete with various challenges that continue to change from year to year. According to Ki Hajar Dewantara, the three educational centers that have an important role in human life are family education, schools and youth movement natural education. Good and harmonious relationships between schools, parents and the community can create schools that are able to compete with schools in their environment. The aim of writing this article was to see to what extent the influence between schools, parents and society is able to influence improving the quality of a school, using literature study methods from various sources. From this research we can conclude that good management between schools, parents and the community can improve the quality of a school.